Adaptación agronómica de seis variedades de cebada (Hordeum vulgare l.), en dos densidades de siembra con proyección para la industria cervecera, en la localidad de Moraspamba, cantón San Miguel, provincia Bolívar - Molina Galeas, Cristian Antonio (2022)
This research was carried out in the town of Moraspamba, owned by Mr. Cristian Molina. The objectives of this research were: Identify the morphological and agronomic characteristics of 6 varieties of barley, Determine the agronomic efficiency of two planting densities in barley, Establish the economic analysis in the cost/benefit ratio. Using a Randomized Complete Block Design (RCBD) with 12 treatments and 3 replications. It is evident that 100% of the barley varieties presented an erect growth habit, in the spike density, 83% presented a lax density, and 17%, which corresponded to the Alpha variety, presented a dense density. In the character type of spike, 83% presented a type of spike dística (2 rows), and the remaining 17% a type of spike Hexastic (6 rows). The Alpha variety had the best average with 51 grains per ear, while the Palmira variety had the lowest number of grains with 18. The best plot yield was for the Alpha variety with 6.58 kg/ha, and the lowest average was for the Metcalfe variety with 4.69 kg/ha. In factor A it can be seen that there were highly significant statistical differences, however it can be noted that the barley varieties Palmira with 3619.2 kg/ha and Alpha with 3230.70 kg/ha presented the best yields, while in factor B, which corresponds to planting densities, there were no statistical differences, However, the density with the best average yield was the 135 kg/ha with 2882.68 kg/ha, while the 100 kg/ha had 2694.22 kg/ha, with a difference between the two densities of 188.45 kg/ha. Economically, the Palmira variety was the one with the best yield with 3619.2 kg/ha, thus providing a benefit-cost ratio of $2.03, which shows that the producer for each dollar invested in the crop has a profit of $1.03, corresponding to a profit of 103%.